PENCATATAN KEUANGAN RUMAH TANGGA: BEBAS PUSING ATUR UANG BULANAN PADA RADIO BHARABAS 97,5 FM PEKANBARU - Nurhasanah, Dinna; Nelaz, Yolanda Safitri; Afriyani, Neni (LPPM Universitas Awal Bros, 2025)
This community service program aims to enhance public literacy and skills in managing household finances through the implementation of effective financial record-keeping practices. A common problem many households face is the inability to systematically manage cash flow, difficulty tracking expenses, and a lack of planning to achieve both short-term and long-term financial goals. This often leads to financial stress and reliance on debt. The selection of this topic is based on the urgency of equipping the public with practical basic personal accounting skills, given the importance of financial stability as the foundation of family well-being.The method of implementing this service focuses on interactive education and direct workshops, specifically designed to facilitate understanding of basic concepts in recording income and expenses, creating realistic budgets, and identifying priority spending categories. The material is delivered using easy-to-understand, straightforward language relevant to daily experiences. The workshops also include simulations of financial record-keeping practices using simple tools, such as manual cash books or free mobile applications, to ensure that the skills taught can be directly applied. The results of the service show a significant improvement in participants' understanding of the importance of financial record-keeping, as well as positive changes in their daily money management behavior. Many participants reported feeling